2017
DOI: 10.1136/bmjresp-2017-000250
|View full text |Cite
|
Sign up to set email alerts
|

International perception of lung sounds: a comparison of classification across some European borders

Abstract: IntroductionLung auscultation is helpful in the diagnosis of lung and heart diseases; however, the diagnostic value of lung sounds may be questioned due to interobserver variation. This situation may also impair clinical research in this area to generate evidence-based knowledge about the role that chest auscultation has in a modern clinical setting. The recording and visual display of lung sounds is a method that is both repeatable and feasible to use in large samples, and the aim of this study was to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…As there is no suitable 'gold standard' benchmark for identifying the presence or absence abnormal breath sounds, we used careful audio and spectrogram analysis of real-world, in-hospital recordings to determine this, with validation by a second blinded clinician who applied the same strict labelling criteria demonstrating excellent interrater agreement. Although human expert labelling may introduce potential bias, previous multicenter research has shown that this approach is a method suitable for research of lung sounds [5]. Nevertheless, due to the absence of a true gold standard, we report our results using PPA and NPA, rather than the more familiar terms sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As there is no suitable 'gold standard' benchmark for identifying the presence or absence abnormal breath sounds, we used careful audio and spectrogram analysis of real-world, in-hospital recordings to determine this, with validation by a second blinded clinician who applied the same strict labelling criteria demonstrating excellent interrater agreement. Although human expert labelling may introduce potential bias, previous multicenter research has shown that this approach is a method suitable for research of lung sounds [5]. Nevertheless, due to the absence of a true gold standard, we report our results using PPA and NPA, rather than the more familiar terms sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, stethoscopes capable of digitally recording breath sounds have become more widely available, offering the ability to capture breath sounds with superior sound quality and fidelity [4]. However, human interpretation of the digital recordings can still exhibit significant inter-listener variability [5]. As the soundwave properties of pathologic breath sounds such as crackles, wheezes and rhonchi have been well-studied and previously defined, computer algorithms and programs to automatically detect them have been developed [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, an acceptable approach is to ask observers Open access to describe audio or visual displays of lung sounds. [6][7][8][9][10] Using this method, studies of lung sound nomenclature have shown that lung terminology varies widely among physicians, residents and physiotherapists working in the same hospital [6][7][8] or in different countries. 9 Interestingly, agreement on the detailed classification of crackles and wheezes was found to be poor, improving when the two terms were combined into broader categories.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Using this method, studies of lung sound nomenclature have shown that lung terminology varies widely among physicians, residents and physiotherapists working in the same hospital [6][7][8] or in different countries. 9 Interestingly, agreement on the detailed classification of crackles and wheezes was found to be poor, improving when the two terms were combined into broader categories. 10 At closer inspection, data from these studies suggest that, while part of the interobserver variation in terminology results from observer preferences (ie, disagreement between correct raters-eg, use of 'rales' or 'crackles'), part might result from lack of auscultatory skill (ie, disagreement due to incorrect sound classification-eg, use of 'normal breath sound' in presence of 'bronchial breathing').…”
Section: Introductionmentioning
confidence: 99%
“…Andrés et al 12 found that the spectrograms Methods Data for classification. The sound recordings employed in this study were also used in the study of Aviles-Solis et al 13 . The description of the sound recording method is therefore the same as in the mentioned study.…”
mentioning
confidence: 99%